The Synthesis of Agar Silicone Biocomposite and Its Mechanical Properties - Nadiah Azmi, Nurul; Mahmud, Jamaluddin; Juzaila Abd Latif, Mohd (International Journal of Engineering and Technology, 2018)
Silicone rubber is widely used in the medical field, whereas agar is widely used as a medium to breed bacteria or to carry the active ingredient for a specific purpose. There are few synthetic skins available in the market that are made of silicone, such as Biobrane, Integra and Transcyte, to name a few. Meanwhile, in a previous study, agar is used to carry the active ingredients in turmeric to the wounded skin and expedite its recovery. However, up to date, there is no available skin substitute with the ability for carrying bioactive ingredient that would expedite wound healing and anti-bacterial properties. Hence, this study aims to synthesise a new biocomposite that could mimic skin mechanical properties with the future potential to carry bioactive ingredient via agar particles. The material constants for this newly developed agar slicone biocomposite are determined using Neo- Hookean, Mooney-Rivlin and Ogden models. This research consists of two main stages; which is the synthesis and the determination of the mechanical properties of agar silicone biocomposite, via experimental and numerical approach. The experimental approach involves testing the biocomposite under uniaxial tensile test, while the numerical approach involves curve fitting method using a Matlab programme. The calculated parameter for Neo-Hookean (C1) ranges from 52-57 kPa for all variances of agar silicone biocomposite. As for Mooney-Rivlin, the values are of 34-38 kPa and 47- 54 kPa for C1 and C2 re spectively. Ogden parameters (Ogden coefficient, Âµ and Ogden exponent, Î±) for agar silicone biocomposites are 48-54 kPa; 2.17-2.19 (Âµ;Î±). The material constants of agar silicone biocomposites lays within the range of human tissue and skin, as well as animal skin; thus proving that agar silicone biocomposite could deform nearly the same as skin. Therefore, it can be concluded that this study has significant contribution to better understand the mechanical properties of the newly developed agar silicone biocomposite.Â